Effect of Alkali (Naoh) Treatment on the Mechanical Properties of Abaca Fiber and Nylon Ropes in Engineering Materials Learning - Melda_Sari_Erawati Melda Sari; Sunardi; Hamdan Akbar Notonegoro; Mohamad Abror; Hidayat; Febri Ramadhoni Saputra; Try Nova Abellia (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2026)
This study aims to analyze the effect of NaOH alkali treatment on the mechanical properties of ropes made from abaca fiber and to compare them with nylon ropes and hybrid abaca–nylon ropes. The abaca fibers were treated using 5% NaOH solution for 4 hours and 10% NaOH solution for 2 hours at room temperature. The fibers were then twisted into three-strand ropes with a length of 80 cm. Tensile testing was conducted using a 100 kN Universal Testing Machine (UTM) at a crosshead speed of 10 mm/min. The test results showed that nylon rope exhibited the highest tensile strength, followed by hybrid abaca–nylon rope, while abaca rope showed the lowest value. The 5% NaOH treatment tended to provide better mechanical performance compared to the 10% NaOH treatment. Excessive alkali concentration caused a decrease in tensile strength due to degradation of the abaca fiber structure.This study also contributes to the field of Mechanical Engineering Education Study Program, particularly in engineering materials and material testing learning. The findings can serve as a learning reference regarding the utilization of natural fibers as environmentally friendly materials and the effect of chemical treatment on the mechanical properties of materials. In addition, this research supports the development of students’ competencies in understanding material characterization, manufacturing technology, and the application of natural fiber-based composite materials in the field of mechanical engineering.